Multi-locus molecular phylogenetic analysis reveals four new species and a new record of Ophiocordyceps (Ophiocordycipitaceae, Hypocreales) on dipteran hosts in Thailand - Suchada Mongkolsamrit; Donnaya Thanakitpipattana; Wasana Noisripoom; Kanoksri Tasanathai; Kanraya Liangsiri; Somruetai Jaiyen; Nattawut Rungjindamai; Marc Stadler; Jennifer Luangsa-ard (MycoKeys)
During field surveys conducted in various regions of Thailand, several fungal specimens parasitising flies were discovered. These fungi exhibited morphological characteristics consistent with the broad concept of Ophiocordyceps dipterigena, including yellow to orange-brown cylindrical stromata bearing fertile ascomata at the tip. Multi-locus phylogenetic analyses based on ITS, LSU, TEF1, and RPB2 sequences revealed that these specimens belong to a well-supported monophyletic clade, referred to as the 'O. dipterigena' complex, which forms a distinct subclade within the hymenostilboid clade. This complex comprises four newly described species with clearly defined host associations: O. floriformis, found on robber flies (Asilidae), particularly on Clephydroneura sp.; O. muscae, isolated from the housefly (Musca domestica); O. tabani, parasitising horse flies (Tabanus sp.); and O. thilosuensis, infecting fruit flies (Anastrepha obliqua) and soldier flies (Sarginae). Additionally, several strains clustered with the previously described O. philippinensis, which was also collected from Clephydroneura sp. This marks the first record of O. philippinensis in Thailand.